Anti-angiogenic properties of Cymbopogon citratus and Moringa oliefera using the chorioallantonic membrane vascular assay - Aldeguer, Justine Joy A.; Canonero, Katrina Anne M. (2012.)
In the Philippines, the use of complementary and alternative medicine, such as plants, is beginning to become very common due to rapidly increasing incidence of cancer in the country. These include lemongrass (Cymbopogon ciratus) and malunggay (Moringa oleifera). However there had been scanty literature to prove these claims. The aim of this study is to screen the methanol extracts of C. citratus and M. oleifera leaves for anti-angionic property using Chorioallantoic Membrane Vascular Assay (CAMVA). Non-lethal concentrations of the plant extracts were embedded into filter paper disks and inserted into the chorioallantoic membrane of the ten-day-old duck embryos. A negative control group of duck eggs were left unopened. After 48 hours of incubation, the number of blood vessels in the chorioallantoic membrane of the duck embryos was manually counted using a dissecte microscope. Results showed that extracts of M. oleifera and C. citratus were able to inhibit blood vessel growth in the chorioallantoic membrane duck embryo. Between the two plants, crude methanol extracts of M. oleifera (12.10+- 0.836) showed a lesser number of developed blood vessels than the crude methanol extracts of C. citratus (14.50+-0.637). The anti-angionic properties of theseplant extracts could be attributed to the presence of phytochemicals such as citral, quercetin, kaempferol, and niazimicin which have been proven to have anti-cancer properties. In conclusion, M. oelifera and C. citratus have anti-angiogenic properties hence they are potential sources of natural treatment for tumor.
Special Problem (Undergraduate, Bachelor of Science in Public Health)College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Cymbopogon citratus -- Anti-angiogenic properties; Moringa oliefera -- Anti-angiogenic properties